Case report: Case series of isolated acute pericarditis after SARS-CoV-2 vaccinations - Ochs, Marco M.; Haass, Markus; Hagstotz, Saskia; Giusca, Sorin; Korosoglou, Grigorios (Frontiers in Cardiovascular Medicine, 2022)
During the worldwide ongoing immunization campaign against SARS-CoV-2, growing data on very rare but potentially harmful side effects of such vaccines arise since approval trials have not been adequately powered to detect those events. Besides the already reported vaccine-related myocarditis, which primarily occurs in young male individuals, our attention was recently drawn to a series of older male and female patients, who were referred to our institutions with isolated acute pericarditis without myocardial damage, shortly after SARS-CoV-2 vaccination. We describe a series of five adult patients presenting with chest pain, shortness of breath and isolated pericarditis with and without pericardial effusion after SARS-CoV-2 vaccination. All patients underwent echocardiography and cardiac magnetic resonance, and the corresponding findings, including late gadolinium enhancement (LGE) and T1 and T2 mapping are reported herein. To our knowledge, such cases have not been systematically reported in the current literature so far.